Cruxes for visual domain sonification in digital arts. Issue 4 (2nd October 2021) - Trček, Denis
ABSTRACT: Two main types of human perception are seeing and hearing. They play a central role in everyday life, scientific research, and also fine arts. Especially in the visual arts, linking the auditory and the visual realms is not uncommon. However, when it comes to linking the visual domain with the audio domain, the possibilities there are less addressed. Therefore, in this paper, we conceptualize the so-called cruxes for sonification of the visual domain. These are hierarchically structured transformations of the main elements in both domains, starting at the physics level, then extending to the physiological level, and finally to the artistic level. They offer a strong basis for creative sonification efforts and are intended for computer-based (generative) art production. In brief, this paper shows that sonification has a strong potential for artistic sonic creations, where scientific basis can play an important role, when linking the visual, acoustic, and physiological domains.